Effect Of Five Finger Relaxation Intervention On Fatigue In Ca Mammae Clients - Probowati, Rovica; Buyu prakoso, Adi; Mei Astuti, Andriana; Aboo Bakkar, Zainie; Nur Azizah, Anisa (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Background: fatigue is the most disturbing sign and symptom felt by cancer patients. As a result of fatigue, clients become too tired to engage in daily activities so that it can affect the client's quality of life. It is necessary to know the factors that have the most significant relationship with fatigue in cancer clients and appropriate nursing interventions are needed to overcome it. Objective: this study was to determine the factors that have the most significant relationship with fatigue in cancer clients and to determine the effect of five-finger relaxation technique intervention on fatigue. Method: research with pre-test and post-test design with 32 respondents with purposive sampling. Data analysis using paired t-test, wilcoxon and spearman correlation. Results: the study showed that sleep quality had a significant relationship with fatigue (p value = 0.004), and the five-finger relaxation technique had an effect on improving sleep quality and decreasing fatigue in ca mammae clients (p = 0.000). Sleep quality and fatigue have a moderate relationship (r = 0.396) and a positive pattern. Conclusion: this study recommends the need to use the five-finger relaxation technique to overcome sleep quality disorders and fatigue as symptoms and signs that are often found in cancer clients.